Der rot-grüne Einstieg in den Abschied vom „Modell Deutschland“: Ein Erklärungsversuch - Beck, Stefan; Scherrer, Christoph (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2005)
Contrary to popular headlines of reform deadlock in Germany, substantial economic reforms have taken place in the past few years. First, we analyze the impact of these reforms on the institutional features of the Modell Deutschland. Second, we ask why the red-green government abandoned the original agenda that favored the core constituency of the coalition government and adopted the unpopular Agenda 2010. For an answer to these questions we turn to theories of hegemony for an explanation of the broader context in which the events have un folded. Within this context, we will explore the actors behavior from a Machiavellian perspective. Our main thesis is that when the left is on the defensive because of a lack of mobilization capabilities, a left-of-center coalition government will feel under pressure to veer to the middle.